Micro-Teaching and Collaborative Learning: A Synergy for Developing Student-Teacher Performance and Collaborative Skills - Amala Malik; Fitrotun Maulani; Farikah; Dwi Winarsih (Universitas Tidar, 2024)
Micro-teaching, one of the valuable advancements in teacher training, has become a tool for student-teachers to achieve professional teaching skills and foster deeper teaching knowledge. Collaborative skills, considered one of the 21st-century skills, have been identified as an indicator of a successful life. Therefore, Collaborative learning as a teaching approach where students work together on tasks or projects can help develop collaborative skills. Equally important, this research investigates how collaborative learning impacts student-teacher performance and collaborative skills development in micro-teaching classrooms, identifying factors contributing to successful teaching practice. This study employs qualitative research using a case study design by collecting data through questionnaires, documentation, and peer observation. The researchers analyzed 70 student-teachers from the micro-teaching class at Universitas Tidar who had already completed the teaching practice. Descriptive qualitative techniques are used to analyze the data to gain a deeper understanding of the results through data condensation, display, and conclusions. As a result, researchers expect to find that collaborative learning significantly enhances student teaching practice performance in the micro-teaching classroom. Furthermore, students could enhance communication, teamwork, management, problem-solving skills, and active participation during the collaborative learning process.